An Education Benefits of Millennials Students at Perbanas Institute Jakarta - Ignatius Septo Pramesworo; B.M.A.S. Anaconda Bangkara; Rosijanih Arbie; Laros Tuhuteru; Khasanah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This study aimed at interviewing university students of Perbanas Institute Jakarta; through focus group discussion interviews, we have received inputs in the form of accurate information about the advantages and benefits students get when they enroll in the institute's banking and finance department. After collecting the data, we analyzed it to understand which would answer the study problems mentioned above. As for the first process, we read the touchscreen interview results and then tried it so that we were able to compile a data concept according to the question and answer segments. After a series of data analyses, there are some advantages that students get while studying and preparing for a career, among others. Successful banking is certainly backed up by Technology and supported by faith resources who understand banking theory and practice in an era that is now increasingly millennial. These findings will provide additional information for the development of similar studies in the future. Keywords:  Education Benefits Millennials, Education Benefits, Education for Milennials